Effects of leadership on the effective performance of Ethiopian banking industry - Debebe Alemu Kebede; Kenenisa Lemi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The aim of the study was to examine the effect of leadership on organizational performance with specific reference to Commercial banks operate in Jimma Town. To achieve the objectives the study causal type of research and panel design was used to examine effect that leadership exert on the bank’s performance. The primary data sources were leaders on different levels and their subordinate employees while, the secondary data sources were annual report of individual banks. Multifactor Leadership Questionnaire was adapted for collecting the data. The descriptive and inferential analyses was conducted to analyze the collected data. Subsequently, the Random Effect Model was used to investigate the extent of relationship between variables. The study results revealed that the existing leadership brings changes in working environment by inspiring and motivating employees for changes, creation, innovation, to go beyond from what they actually think they can; and reward employees and make recognition in exchange for the work they perform, giving close directions and guidance have positive and significant effect in promoting the performance of the bank. Hence, the leaders of banks should focus on playing a role model and stakeholders in the industry should consider taking banking in a non-traditional.